(untitled) (Marketing Journal, 2025)
This scientific article provides an in-depth analysis of the rational use of marketing strategies in the development of the transport system under regional economic conditions, using the Khorezm region as a case study. The research examines the territorial characteristics of the transport services market, consumer needs and behavior, marketing research, digital marketing tools, and the impact of marketing communications on the efficiency of the transport system. Based on statistical data from 2020 to 2024, scientific conclusions and practical recommendations are formulated to improve marketing approaches in the regional transport services market.